How to Navigate Trainee‐Mentor Relationships and Interpersonal Dynamics in the Lab. Issue 3 (22nd March 2021) - Antes, Alison L.; Maggi, Leonard B.
Abstract: Relationships with mentors and labmates are defining aspects of a researcher's journey in science. Ideally, these interactions are outstanding opportunities to learn from others and provide the basis for lifelong collaborations. Unfortunately, sometimes interpersonal dynamics in the lab are challenging. Graduate students entering the lab can greatly benefit from advice about navigating the interpersonal aspects of doing science. This article covers essential recommendations for developing a good trainee‐mentor relationship and working well with peers in the lab, or being a "good lab citizen." Lab members–especially graduate students–often spend more time with labmates than with their friends and family during their graduate career, making these relationships essential to their well‐being. The guidance also covers some advice for handling a tense relationship or problematic work environment. Finally, the advice concludes by discussing how to manage the fear of failure, overcome imposter syndrome, develop self‐awareness, and cope with stress. These four issues are fundamental to success in research but are not discussed with graduate students as much as may be necessary. © 2021 Wiley Periodicals LLC.